Analysis of Students' Spatial Ability Using GeoGebra in the Spatial Geometry Course - Izzati, Nurma; Farizi, Reo Al (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2025)
This study aims to analyze the spatial ability of students using GeoGebra in solving students' spatial ability problems in the spatial geometry course. The research method used uses a descriptive qualitative method. The instrument used is a spatial ability test of spatial geometry which is arranged based on spatial ability indicators, namely visualization, spatial perception, mental rotation, spatial relation, and spatial orientation. The research subjects used were all students of the Mathematics Department of the Faculty of Tarbiyah and Teacher Training (FITK) semester 3 classes A and B of the State Islamic University of Cyber Syekh Nurjati Cirebon (UIN SSC) totaling 49 students. The results of this study show that the spatial ability of students using GeoGebra in the spatial geometry course is very good with an overall score of 86.5 and a score per indicator, in the visualization indicator of 100, spatial perception of 92.65, mental rotation of 94.28, spatial relation of 53.06, and spatial orientation of 92.65.